Fertilizer Management of Gypsophila (Gypsophila Paniculata) (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was conducted at the research field of Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI) Gazipur under AEZ-28 during Rabi season of 2017-18 and 2018-19 to determine the suitable combination of nitrogen (N), phosphorus (P), potassium (K) and sulphur (S) for improving growth and cut flower bunch yield of gypsophila. There were 15 treatment combinations comprising four levels of nitrogen (0, 70, 100 and 130 kg ha-1), four levels of phosphorus (0, 20, 40 and 60 kg ha-1), four levels of potassium (0, 60, 90 and 120 kg ha-1) and four levels of sulphur (0, 10, 20 and 30 kg ha-1) along with a blanket dose of Zn3B1.5 kg ha-1 and cow dung 5 t ha-1. The experiment was laid out in randomized complete block design with three replications. The combination of N100P40K60S20 kg ha-1 produced significantly higher cut flower bunch yield. The said treatment produced the maximum mean cut flower bunch yield of 185010 nos. ha-1 which was 76.9% higher over control (N0P0K0S0). The maximum number of branches per plant (7.12 nos.) and maximum opened flower per plant (60.2 nos.) were recorded from the treatment combination of N100P40K60S20 kg ha-1. Cost and return analysis indicated maximum net return and highest benefit cost ratio (1.91) was estimated from the same treatment. The results suggest that combined application of 100-40-60-20 kg ha-1 of N-P-K-S including 3 kg Zn ha-1, 1.5 kg B ha-1 and 5 t ha-1 cowdung can improve the growth and cut flower bunch yield of gypsophila. From the regression analysis, the optimum treatment combination was calculated as N91.8P44.0K80.7S18.7 kg ha-1 for experimental area. Therefore, the optimum combination package N91.8P44.0K80.7S18.7 kg ha-1 along with the blanket dose of Zn3B1.5 kg ha-1 and 5 t cowdung ha-1 may be recommended for gypsophila cut flower cultivation in Gazipur area.Bangladesh J. Agril. Res. 46(1): 23-34, March 2021